The case of the Royal Spanish House: a stage in transformation (1978-2013) (2015)
Since the restoration of the monarchy in Spain thanks to the approval of the Constitution in 1978, the Royal Spanish House has had some of the most opaque and arbitrary communicative management in the world. After the analysis of nearly 4000 news items published about King Juan Carlos I in the years 2009 to 2012, this article will describe an organizational transformation which is being adopted by the Royal Spanish House. In the context of the digital era, the institution is implanting many managerial tools that can be identified from two axes of comprehension: 1) the communication of the dimensions of the Crown according to a hybrid model of strategies persuasive-informative; and, 2) the progressive creation of politics of active transparency on the routines of the institution.